Global transmission and evolutionary dynamics of the Chikungunya virus. (19th February 2020) - Deeba, F.; Haider, M. S. H.; Ahmed, A.; Tazeen, A.; Faizan, M. I.; Salam, N.; Hussain, T.; Alamery, S. F.; Parveen, S.
Abstract: Chikungunya virus (CHIKV) is a re-emerging pathogen of global importance. We attempted to gain an insight into the organisation, distribution and mutational load of the virus strains reported from different parts of the world. We describe transmission dynamics and genetic characterisation of CHIKV across the globe during the last 65 years from 1952 to 2017. The evolutionary pattern of CHIKV was analysed using the E1 protein gene through phylogenetic, Bayesian and Network methods with a dataset of 265 sequences from various countries. The time to most recent common ancestor of the virus was estimated to be 491 years ago with an evolutionary rate of 2.78 × 10 −4 substitutions/site/year. Genetic characterisation of CHIKV strains was carried out in terms of variable sites, selection pressure and epitope mapping. The neutral selection pressure on the E1 gene of the virus suggested a stochastic process of evolution. We identified six potential epitope peptides in the E1 protein showing substantial interaction with human MHC-I and MHC-II alleles. The present study augments global epidemiological and population dynamics of CHIKV warranting undertaking of appropriate control measures. The identification of epitopic peptides can be useful in the development of epitope-based vaccine strategies against this re-emerging viral pathogen.